Pengaruh Likuiditas, Leverage, Profitabilitas, dan Ukuran Perusahaan Terhadapa Nilai Perusahaan Pada Sub Sektor Food and Beverage Yang Terdaftar di Bursa Efek Idonesia - Gunawan, Agung (Visioner : Jurnal Manajemen dan Bisnis, 2025)
This research aims to determine the effect of liquidity (current ratio), leverage (debt to equity ratio), profitability (return on assets) and firm size (Ln total assets) on company value (price earning ratio) of the food and beverage sub sector listed on the Indonesia Stock Exchange for the period 2019-2023. This research employs a quantitative approach. The sampling technique chosen as the research sample. Data analysis was conducted using IBM SPSS version 25, incorporating descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The research results shows that the current ratio partially has a positive and significant effect on the price earning ratio. The debt to equity ratio partially has no negative and insignificant effect on the price earning ratio. Return on assets partially has a positive and significant effect on the price earning ratio. Ln total assets does not partially have a positive and insignificant effect on the price earning ratio. Futhermore, the current ratio, debt to equity ratio, return on assets and Ln total assets simultaneously and significantly influence the price earning ratio